Condition monitoring of Electrical Submersible Pumps (Faults review) - Al-Hashmi, Salem. A. (Journal of Pure & Applied Sciences, 2021)
This paper is a part of condition monitoring of electrical submersible pumps (ESP). It assigned for reviewing and discussing faults or malfunctions of this kind of pumps. Therefore, it reviews all-important information related to this machine such as construction and operation. It focuses specifically on faults and details of these types of fault. Although there are slight differences between building submersible pumps in terms of the different technologies that different manufacturers use in making this type of pump, all kinds of these types of pumps are almost the same. In this context, pumps faults were reviewed based on major and common failures of this type of pumps.